Exocentric Pointing in the Visual Field. (December 2013) - van Doorn, Andrea; Koenderink, Jan; Wagemans, Johan
"Exocentric pointing in the visual field" involves the setting of a pointer so as to visually point to a target, where both pointer and target are objects in the visual field. Phenomenologically, such pointings show systematic deviations from veridicality of several degrees. The errors are very small in the vertical and horizontal directions, but appreciable in oblique directions. The magnitude of the error is largely independent of the distance between pointer and target for stretches in the range 2–27°. A general conclusion is that the visual field cannot be described in terms of one of the classical homogeneous spaces, or, alternatively, that the results from pointing involve mechanisms that come after geometry proper has been established.